Xylem growth cessation in stems and branches of European beech and silver birch: influences of temperature and drought - Marchand, Lorène J.; Gričar, Jožica; Prislan, Peter; Dox, Inge; Verlinden, Melanie; Flores, Omar; Campioli, Matteo (Frontiers in Plant Science, 2025)
IntroductionAssessing wood growth phenology over multiple years is essential for understanding the environmental drivers of forest growth and improving large-scale predictions of the carbon cycle. Xylogenesis methods facilitate the assessment of the timing and rate of xylem cell wall thickening, the primary sink of carbon in wood. In angiosperm trees, where wood anatomy is complex, significantly less is known about the factors controlling growth cessation in autumn due to indirect, sinteracting, and lag effects, in contrast to growth resumption in spring. Furthermore, both branch and stem growth must be considered to account for the total aboveground phenology. MethodsIn this study, we focused on European beech (Fagus sylvatica) and silver birch (Betula pendula) in a mild temperate region (Northern Belgium). We examined the progress of cell wall thickening in autumn and the seasonal timing of xylem growth cessation for these species’ stems over five years and for their branches over one year in mature trees. In addition, we investigated the same variables in the stems and branches of potted saplings for two years and for oak (Quercus robur) and aspen (Populus tremula) saplings over one year.ResultsOur results demonstrate a considerable variation in the progression and cessation of wood growth, with differences of up to a month and a half in growth cessation (early September to late October), predominantly driven by climatic variables. Early cessation of xylem growth in stems was strongly associated with high temperatures in April and August, elevated vapour pressure deficit, and severe soil drought in August. The progression of cell wall thickening in late summer was generally synchronized between branches and stems for every species. However, branches sustained a higher percentage of growth (approximately 2 weeks) in early autumn during non-drought years. DiscussionThese findings provide valuable insights for refining models of forest growth and carbon storage, enabling a more comprehensive representation that encompasses the entire tree under different climatic scenarios.